Accounting: Basic Principles and Applications - J.Guerrieri Donald (Mc Graw Hill Irwin, 1992)
Designed for use in a one-semester course, this text offers a thorough introduction to basic accounting procedures. Numerous illustrations and examples guide students through accounting procedures. In-chapter activities reinforce student understanding of the material. “Remember” notations highlight important chapter concepts. A variety of questions, skill-building activities, exercises, and problems give students the opportunity to apply accounting procedures.